Defining the boundaries and operational concepts of resilience in the resilience in healthcare research program - Siri Wiig; Karina Aase; Stephen Billett; Carolyn Canfield; Olav Røise; Ove Njå; Veslemøy Guise; Cecilie Haraldseid-Driftland; Eline Ree; Janet E. Anderson; Carl Macrae; on behalf of the RiH-team (BMC, 2020)
Abstract Background Understanding the resilience of healthcare is critically important. A resilient healthcare system might be expected to consistently deliver high quality care, withstand disruptive events and continually adapt, learn and improve. However, there are many different theories, models and definitions of resilience and most are contested and debated in the literature. Clear and unambiguous conceptual definitions are important for both theoretical and practical considerations of any phenomenon, and resilience is no exception. A large international research programme on Resilience in Healthcare (RiH) is seeking to address these issues in a 5-year study across Norway, England, the Netherlands, Australia, Japan, and Switzerland (2018-2023). The aims of this debate paper are: 1) to identify and select core operational concepts of resilience from the literature in order to consider their contributions, implications, and boundaries for researching resilience in healthcare; and 2) to propose a working definition of healthcare resilience that underpins the international RiH research programme. Main text To fulfil these aims, first an overview of three core perspectives or metaphors that underpin theories of resilience are introduced from ecology, engineering and psychology. Second, we present a brief overview of key definitions and approaches to resilience applicable in healthcare. We position our research program with collaborative learning and user involvement as vital prerequisite pillars in our conceptualisation and operationalisation of resilience for maintaining quality of healthcare services. Third, our analysis addresses four core questions that studies of resilience in healthcare need to consider when defining and operationalising resilience. These are: resilience 'for what', 'to what', 'of what', and 'through what'? Finally, we present our operational definition of resilience. Conclusion The RiH research program is exploring resilience as a multi-level phenomenon and considers adaptive capacity to change as a foundation for high quality care. We, therefore, define healthcare resilience as: the capacity to adapt to challenges and changes at different system levels, to maintain high quality care. This working definition of resilience is intended to be comprehensible and applicable regardless of the level of analysis or type of system component under investigation.